In vivo optical interrogation of neuronal responses to genetic, cell type-specific silencing - Terzi, Firat; Knabbe, Johannes; Cambridge, Sidney (The journal of neuroscience, 2023)
We established a low background, Cre-dependent version of the inducible Tet-On system for fast, cell type-specific transgene expression in vivo. Coexpression of a constitutive, Cre-dependent fluorescent marker selectively allowed single-cell analyses before and after inducible, Tet-dependent transgene expression. Here, we used this method for precise, acute manipulation of neuronal activity in the living brain. The goal was to study neuronal network homeostasis at cellular resolution. Single induction of the potassium channel Kir2.1 produced cell type-specific silencing within hours that lasted for at least 3 d. Longitudinal in vivo imaging of spontaneous calcium transients and neuronal morphology demonstrated that prolonged silencing did not alter spine densities or synaptic input strength. Furthermore, selective induction of Kir2.1 in parvalbumin interneurons increased the activity of surrounding neurons in a distance-dependent manner. This high-resolution, inducible interference and interval imaging of individual cells (high I5, HighFive) method thus allows visualizing temporally precise, genetic perturbations of defined cells. - SIGNIFICANCE STATEMENT Gene function is studied by KO or overexpression of a specific gene followed by analyses of phenotypic changes. However, being able to predict and analyze exactly those cells in which genetic manipulation will occur is not possible. We combined two prominent transgene overexpression methods to fluorescently highlight the targeted cells appropriately before cell type-specific transgene induction. By inducing a potassium channel that decreases neuronal firing, we investigated how neuronal networks in the living mouse brain possibly compensate swift changes in cellular activities. Unlike in vitro, known compensatory homeostatic mechanisms, such as changes in synapses, were not observed in vivo. Overall, we demonstrated with our method rapid genetic manipulation and analysis of neuronal activities as well as precision transgene expression.
Gesehen am 23.07.2024